Towards "bionic" proteins: replacement of continuous sequences from HIF-1α with proteomimetics to create functional p300 binding HIF-1α mimics. Issue 31 (24th March 2016) - Burslem, George M.; Kyle, Hannah F.; Breeze, Alexander L.; Edwards, Thomas A.; Nelson, Adam; Warriner, Stuart L.; Wilson, Andrew J.
Abstract : An extended sequence of α-amino acids in HIF-1α is replaced with a non-natural topographical mimic of an α-helix comprised from an aromatic oligoamide to reproduce its p300 recognition properties. Abstract : Using the HIF-1α transcription factor as a model, this manuscript illustrates how an extended sequence of α-amino acids in a polypeptide can be replaced with a non-natural topographical mimic of an α-helix comprised from an aromatic oligoamide. The resultant hybrid is capable of reproducing the molecular recognition profile of the p300 binding sequence of HIF-1α from which it is derived.